Making markets just: Reciprocity violations as key intervention points - Oliver Richters; Andreas Siemoneit (ZOE. Institut für zukunftsfähige Ökonomien, 2021)
Worldwide, politics are challenged to achieve economic stability, socialjustice, and ecological sustainability. These goals are often played offagainst each other,and some suspect that market economies (aka capitalism) are basically unable to solvethese dilemmas. This article explores the normative foundations of market economy asa robust, self-regulating system enabling just exchange in large (anonymous) groups.The primary principle of justice for market exchange is reciprocity, i.e., the balanceof costs and benefits from any kind of social exchange. The corresponding socialnorm is calledMeritocratic Principle. It can be implemented and its contestednessavoided by concentrating on "non-merit", i.e., institutionally draining the wellspringsof systematically undeserved incomes (economic rents). Economic rents as violationsof reciprocity can be viewed as a key problem of justice in any economic system. Thispolitical compass can guide consistent policy measures and is applied to two economichot spots: land rents and resource consumption. The measures discussed follow theGerman neo-liberal ideal of an "economic order" by setting only few general caps.This improves stability, justice and sustainability of market economies and makes theliberal vision of self-regulating markets more realistic.
Keywords: 330; market economy; justice; reciprocity; economic rents; liberalism; growth imperative